2020
DOI: 10.3390/cells10010005
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of Embryonic Macrophages Leads to a Reduction in Angiogenesis in the Ex Ovo Chick Chorioallantoic Membrane Assay

Abstract: Macrophages play an important but poorly understood role in angiogenesis. To investigate their role in vessel formation, relevant in vivo models are crucial. Although the chick chorioallantoic membrane (CAM) model has been frequently used as an angiogenesis assay, limited data are available on the involvement of chicken macrophages in this process. Here, we describe a method to deplete macrophages in the ex ovo chick CAM assay by injection of clodronate liposomes and show that this depletion directly affects v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Chicken embryonic macrophages play an important role in angiogenesis. Earlier study with the chicken CAM model indicated the importance of macrophages for neovascularization of implants on the CAM [ 28 ]. We conclude that their presence is a sign of new vessels formation in the surrounding area of implanted PHB/CHIT scaffold.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chicken embryonic macrophages play an important role in angiogenesis. Earlier study with the chicken CAM model indicated the importance of macrophages for neovascularization of implants on the CAM [ 28 ]. We conclude that their presence is a sign of new vessels formation in the surrounding area of implanted PHB/CHIT scaffold.…”
Section: Resultsmentioning
confidence: 99%
“…WGA bounds well to the luminal surface of vessels; therefore, it can be effectively used as a marker for the visualization of the vessels of early stages of the embryo development [ 58 ]. An important role in the body immune response and in developmental angiogenesis of the embryo is undertaken by macrophages, which have been demonstrated to express pro-angiogenic markers [ 28 ]. Macrophages are found when angiogenesis and inflammation occur [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Angiogenesis is well-accepted to occur alongside inflammation. 80 Resident cells such as macrophages, dendritic cells, lymphocytes, and microglia promote angiogenesis and anastomosis during zebrafish development, 81 collateral vessel growth, 82 macular degeneration, 83 chick CAM assays, 84,85 retinal angiogenesis, 81 and developmental and pathological angiogenesis. 86,87 Leukocytes secrete angiogenic factors, including chemokines and VEGF.…”
Section: Discussionmentioning
confidence: 99%
“…Recruitment of macrophages can induce angiogenesis to enhance nerve regeneration [ 133 ]. In addition, reduction or depletion of macrophages suppresses angiogenesis [ 134 ]. Tumor-derived exosomes (TEX) are capable of carrying CD39/CD73 and adenosine, which are enzymatically active.…”
Section: Exosomes and Tumor Angiogenesismentioning
confidence: 99%